Co-operative Investment policy for Growth and Development of Small and Medium Size Businesses and Improve the Poverty Condition in Bangladesh - Hossain, Md. Nazmul; Hassan, Md. Mehedi (European Scientific Journal, ESJ, 2020)
The research focuses on the assessment of SMEs (Small and Medium Size Enterprises) & its impacts on socio-economic spheres; it focuses on the effective ways for growth & development of SMEs in Bangladesh for socioeconomic development. Bangladesh is one of the poorest countries in the world with low GDP/capita and minimum purchasing power. 24.8% of the total population of the country does live below the national poverty line (2/day), while 6.5% of them do live in extreme poverty [4]. To bring the vast population out of the vicious circle of poverty and accelerate the economic growth are the target and attention of the country. To pave the way for first & foremost task is either to create direct employment or create condition to create employment to reduce the unemployment rate & accelerate the source and level of disposable income. Growth & development of SMEs, which create self-employments and employments for low and semi-skilled workers, are the target and attention of the country. But the ways for growth & development of SMEs in Bangladesh are not smooth enough. They are frequently confronted with structural, managerial, financial, and social challenges. For sustainable development large population groups are needed to get the ways for their own development. The research was conducted by structural and semi-structural questionnaires and face-to-face interview of 150 recipients of social classes and ages in rural and urban areas in Bangladesh. The aim of the paper is to analyze the effect of Co-operative Investment Policy through “Co-operative Society Micro-saving Bank” and ‘’Innovative SME Model’’ for growth and development of SMEs and MIAs (Micro Industrial Activities) and its impacts on socio-economic development. The target is to aggregate impoverished individuals’ micro saving, limited capability, little working skills & experiences to create them depositors, investors, successful entrepreneurs & skills workers through establishing co-operative society micro-saving bank and involving them in entrepreneurial activities.